MyD88 deficiency ameliorates weight loss caused by intestinal oxidative injury in an autophagy‐dependent mechanism. Issue 1 (22nd November 2021) - Qi, Ming; Liao, Simeng; Wang, Jing; Deng, Yuankun; Zha, Andong; Shao, Yirui; Cui, Zhijuan; Song, Tongxing; Tang, Yulong; Tan, Bie; Yin, Yulong
Abstract: Background: Gut health plays a vital role in the overall health and disease control of human and animals. Intestinal oxidative stress is a critical player in the induction and progression of cachexia which is conventionally diagnosed and classified by weight loss. Therefore, reduction of intestinal oxidative injury is a common and highly effective strategy for the maintenance of human and animal health. Here we identify intestinal myeloid differentiation primary response gene 88 (MyD88) as a novel target for intestinal oxidative stress using canonical oxidative stress model induced by paraquat (PQ) in vitro and in vivo . Methods: Intestinal oxidative stress was induced by administration of PQ in intestinal epithelial cells (IECs) and mouse model. Cell proliferation, apoptosis, DNA damage, mitochondrial function, oxidative status, and autophagy process were measured in wild‐type and MyD88‐deficient IECs during PQ exposure. Autophagy inhibitor (3‐methyladenine) and activator (rapamycin) were employed to assess the role of autophagy in MyD88‐deficient IECs during PQ exposure. MyD88 specific inhibitor, ST2825, was used to verify function of MyD88 during PQ exposure in mouse model. Results: MyD88 protein levels and apoptotic rate of IECs are increased in response to PQ exposure ( P  < 0.001). Intestinal deletion of MyD88 blocks PQ‐induced apoptosis (~42% reduction) and DNA damage (~86% reduction), and improves mitochondrial fission (~37% reduction) and function including mitochondrial membrane potential (~23% increment) and respiratory metabolism capacity (~26% increment) ( P  < 0.01). Notably, there is a marked decrease in reactive oxygen species in MyD88‐deficient IECs during PQ exposure (~70% reduction), which are consistent with high activity of antioxidative enzymes (~83% increment) ( P  < 0.001). Intestinal ablation of MyD88 inhibits mTOR signalling, and further phosphorylates p53 proteins during PQ exposure, which eventually promotes intestinal autophagy (~74% increment) ( P  < 0.01). Activation of autophagy (rapamycin) promotes IECs growth as compared with 3‐methyladenine‐treatment during PQ exposure (~173% increment), while inhibition of autophagy (3‐methyladenine) exacerbates oxidative stress in MyD88‐deficient IECs ( P  < 0.001). In mouse model, inhibition of MyD88 using specific inhibitor ST2825 followed by PQ treatment effectively ameliorates weight loss (~4% increment), decreased food intake (~92% increment), gastrocnemius and soleus loss (~24% and ~20% increment, respectively), and intestinal oxidative stress in an autophagy dependent manner ( P  < 0.01). Conclusions: MyD88 modulates intestinal oxidative stress in an autophagy‐dependent mechanism, which suggests that reducing MyD88 level may constitute a putative therapeutic target for intestinal oxidative injury‐induced weight loss.